Bentuk Penyajian Tari Sekapur Sirih di Sanggar Sekintang Dayo Jambi - wati, anggun kartika (Institut Seni Indonesia Yogyakarta, 2024)
The Sekapur Sirih dance originates from Jambi, this dance is a dance to welcome honored guests who come to Jambi. The Sekapur Sirih dance is a group dance danced by 10 female dancers and 2 male dancers, in which 9 female dancers dance, 1 female carrying a cerano and 2 males carrying umbrellas and spears. The Sekapur Sirih dance is only shown at official events to welcome guests. The Sekapur Sirih dance is taken from the Jambi ivory custom of decorating and concocting Sirih. There are many Sekapur sirih dances in Jambi, but there are many differences in the way they are performed, the music, even the costumes. The Sekapur Sirih dance at the Sekintang Dayo Studio has not changed at all, more precisely, there have been many developments from before, where the Sekapur Sirih dance at the Sekintang Dayo Studio was often performed when guests of honor came to Jambi. To solve the problem, this study uses the approach of Y. Sumandiyo Hadi's book Text and Context Studies. The textual approach looks at dance from the form of presentation that can be seen from the performers, the theme, movement, accompaniment, make-up and clothing, the place of performance, while the contextual approach looks at the relationship between dance and the supporting community. This approach is to peel the problem. The accompaniment of the Sekapur Sirih Dance uses Jambi regional songs with musical instruments, namely Rebana, Accordeon, Tambourine, Guitar, Violin. The make-up used is beautiful makeup and uses typical Jambi clothing.